Levinas and the Ambivalence of Recognition - Pöykkö, Panu-Matti (Open theology, 2016)
This paper argues that Emmanuel Levinas’ critique of the "ontological imperialism" does not amount to a perfunctory and rejective attitude towards ontology. Against the commonly held interpretation of Levinas, I argue that if we keep in mind that the understanding of the other is grounded on and determined by ethical recognition of the person, ontological recognition of the other person does not necessarily entail violent relation towards of the other person. Moreover, ethical recognition provides a standard of evaluation for ontological recognition and traditional theological discourse. The distinction between the two forms of recognition is essential to Levinas’ account of "religious life". The two forms of recognition are nevertheless interconnected, if not reducible to one another. It is only when we lose sight of the fundamental ethical perspective that the ontological recognition is in danger of becoming violent and repressive.